Spirometry and volumetric capnography in lung function assessment of obese and normal-weight individuals without asthma - Mariana S. Ferreira; Roberto T. Mendes; Fernando A.L. Marson; Mariana P. Zambon; Maria A.R.G.M. Antonio; Ilma A. Paschoal; Adyléia A.D.C. Toro; Silvana D. Severino; Maria A.G.O. Ribeiro; José D. Ribeiro (Elsevier, 2017)
Objective: To analyze and compare lung function of obese and healthy, normal-weight children and adolescents, without asthma, through spirometry and volumetric capnography. Methods: Cross-sectional study including 77 subjects (38 obese) aged 5-17 years. All subjects underwent spirometry and volumetric capnography. The evaluations were repeated in obese subjects after the use of a bronchodilator. Results: At the spirometry assessment, obese individuals, when compared with the control group, showed lower values of forced expiratory volume in the first second by forced vital capacity (FEV1/FVC) and expiratory flows at 75% and between 25 and 75% of the FVC (p < 0.05). Volumetric capnography showed that obese individuals had a higher volume of produced carbon dioxide and alveolar tidal volume (p < 0.05). Additionally, the associations between dead space volume and tidal volume, as well as phase-3 slope normalized by tidal volume, were lower in healthy subjects (p < 0.05). These data suggest that obesity does not alter ventilation homogeneity, but flow homogeneity. After subdividing the groups by age, a greater difference in lung function was observed in obese and healthy individuals aged >11 years (p < 0.05). Conclusion: Even without the diagnosis of asthma by clinical criteria and without response to bronchodilator use, obese individuals showed lower FEV1/FVC values and forced expiratory flow, indicating the presence of an obstructive process. Volumetric capnography showed that obese individuals had higher alveolar tidal volume, with no alterations in ventilation homogeneity, suggesting flow alterations, without affecting lung volumes. Resumo: Objetivo: Analisar e comparar a função pulmonar de crianças e adolescentes obesos e eutróficos saudáveis, sem asma, pela espirometria e capnografia volumétrica. Métodos: Estudo transversal incluindo 77 indivíduos (38 obesos) com idade entre cinco a 17 anos. Todos os indivíduos realizaram espirometria e capnografia volumétrica. Os obesos repetiram as avaliações após o uso de broncodilatador. Resultados: Na avaliação da espirometria, os indivíduos obesos, quando comparados ao grupo controle, apresentaram menores valores no volume expiratório forçado no primeiro segundo pela capacidade vital forçada (VEF1/CVF) e nos fluxos expiratórios a 75% da CVF e entre 25-75% da mesma (p < 0,05). A capnografia volumétrica demonstrou que os obesos apresentam maior volume produzido de dióxido de carbono e volume corrente alveolar (p < 0,05). Além disso, a relação entre o volume espaço morto e volume corrente, bem como o slope da fase 3 normalizado pelo volume corrente foram menores nos indivíduos saudáveis (p < 0,05). Esses dados sugerem que a obesidade não altera a homogeneidade da ventilação, mas sim dos fluxos. Ao subdividir os grupos por idade, foi observada maior diferença na função pulmonar entre indivíduos obesos e saudáveis na faixa etária acima de 11 anos (p < 0,05). Conclusão: Mesmo sem o diagnóstico de asma por critérios clínicos e sem resposta ao uso de broncodilatador, os indivíduos obesos apresentaram menores valores no VEF1/CVF e nos fluxos expiratórios forçados, indicando a presença de processo obstrutivo. A capnografia volumétrica indicou nos indivíduos obesos maior volume corrente alveolar, sem alterações na homogeneidade da ventilação, sugerindo alteração nos fluxos, sem comprometimento dos volumes pulmonares. Keywords: Capnography, Spirometry, Obesity, Palavras-chave: Capnografia, Espirometria, Obesidade